Photocatalytic aquatic plant fiber for improving water quality of flowing water body and preparation method of photocatalytic aquatic plant fiber
By using nitrogen carbide and titanium dioxide nanoparticle composite materials and photocatalytic aquatic plants fibers of metal ions and artificial fibers in flowing water, the problems of low efficiency and poor stability of existing photocatalytic materials in flowing water are solved, and high efficiency and stability are achieved water purification effect.
Patent Information
- Application Number
- CN202411405116.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing photocatalytic materials have low catalytic efficiency, poor stability, easy deposition and aggregation in flowing water bodies, and have high maintenance costs, making it difficult to effectively purify the water bodies in the long run.
Using a composite material of nitrogen carbide and titanium dioxide nanoparticle, combining metal ions (Zn2+, Cu2+, Co2+) and artificial fibers (polypropylene, non-woven fabrics, cotton fibers), the photocatalytic aquatic fibers are formed through modification treatment and ultrasonic adhesion, ensuring that Efficiently degrade organic pollutants under natural light and maintain material stability.
It significantly improves the photocatalytic efficiency, avoids material deposition and aggregation, enhances the stability and adhesion of the material, is suitable for large-scale water pollution control, is environmentally friendly, and reduces maintenance costs.
Smart Images

Figure CN119303609A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water pollution control, and in particular to a photocatalytic water grass fiber for improving the water quality of flowing water bodies and a preparation method thereof. Background Art
[0002] With the rapid development of industrialization and urbanization, water pollution is becoming increasingly serious, especially in flowing water bodies, where the migration and diffusion of pollutants are more complicated. Pollutants in water bodies mainly include organic pollutants in industrial wastewater, heavy metal ions, nitrogen and phosphorus compounds in agricultural non-point source pollution, and suspended solids in domestic sewage. Once these pollutants enter the water body, they will not only affect the aquatic ecosystem, but also pose a potential threat to human health. Pollution control of flowing water bodies is particularly difficult because water flow will accelerate the spread of pollutants and increase the difficulty of purification.
[0003] Existing water purification methods mainly include physical filtration, chemical precipitation, adsorption, artificial wetlands, etc., but these methods have their own limitations. Although physical filtration can remove larger suspended particles, it is less effective for dissolved organic matter and chemical pollutants; chemical precipitation and adsorption methods are effective for removing heavy metal ions and certain pollutants, but they are prone to secondary pollution and have high treatment costs; artificial wetlands, as a natural purification method, although they have certain ecological restoration functions, occupy a large area and have limited effects on the removal of pollution from flowing water bodies. In addition, these methods are often complex to operate, have high maintenance costs, may have a negative impact on the ecological environment of water bodies, and cannot effectively purify water bodies in the long term.
[0004] Photocatalytic technology has good application prospects because it can generate highly active free radicals through the action of catalysts under light conditions, and further degrade organic pollutants in water. However, existing photocatalytic materials (such as TiO2) still have several problems in practical applications. First, most photocatalytic materials require ultraviolet light excitation, and the catalytic efficiency is low under natural light conditions, which limits the breadth of their practical applications. Secondly, existing photocatalytic materials are easy to deposit or aggregate in water bodies, and it is difficult to maintain an effective dispersed state in water bodies, especially in flowing water bodies, where the stability of catalytic materials is poor. In addition, these materials are prone to photocorrosion during long-term use, the catalytic effect gradually decreases, and the maintenance cost is high.
[0005] Therefore, it is urgent to develop an efficient photocatalytic material that can be applied to flowing water bodies, which can not only achieve effective photocatalytic reaction under natural light, but also maintain the long-term stability of the material, avoid sedimentation and aggregation problems, and have good environmental adaptability and sustainability. This material should be easy to install, simple to operate, and suitable for large-scale water pollution control, thus providing a better solution for the continuous purification of flowing water bodies. Summary of the invention
[0006] The purpose of the present invention is to provide a photocatalytic water grass fiber and a preparation method for improving the water quality of flowing water bodies, which has the advantages of high photocatalytic efficiency, strong material stability, easy distribution and installation, and environmental friendliness, and solves the problem of limited application of existing photocatalytic materials in flowing water bodies.
[0007] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a photocatalytic water grass fiber for improving the water quality of flowing water bodies, the photocatalytic water grass fiber is composed of the following components: a photocatalytic active component group: carbonized nitrogen, titanium dioxide nanoparticles; a function enhancement component group: metal ions; a fiber base material component group: polypropylene fiber, non-woven fiber, cotton fiber; the metal ions include Zn 2+ , Cu 2+ and Co 2+ .
[0008] Preferably, the photocatalytic water grass fiber includes the following components in the content range: nitrogen carbonization: 50%-70%; titanium dioxide nanoparticles: 20%-40%; metal ions: 0.1%-5%; polypropylene fiber: 10%-20%; non-woven fiber: 5%-15%; cotton fiber: 5%-10%.
[0009] Preferably, the specific content range of the optimized formula of the photocatalytic water grass fiber is: nitrogen carbonization: 55%-65%; titanium dioxide nanoparticles: 25%-35%; metal ions: 1%-3%; polypropylene fiber: 12%-18%; non-woven fiber: 8%-12%; cotton fiber: 5%-8%.
[0010] Preferably, the particle size of the titanium dioxide nanoparticles ranges from 10 nanometers to 30 nanometers;
[0011] The specific surface area of the carbonized nitrogen is 80 to 100 m 2 / g, and its particle size is 10 microns to 20 microns;
[0012] The loading amount of the metal ions is 85% to 95% of the total mass of the composite material;
[0013] The diameter of the polypropylene fiber ranges from 0.3 mm to 0.5 mm;
[0014] The water absorption rate of the nonwoven fabric fibers is 90% to 95% of its weight.
[0015] A method for preparing photocatalytic water grass fibers for improving the water quality of flowing water bodies comprises the following steps:
[0016] S1. Modification of carbonitride:
[0017] S1.1 The carbonized nitrogen material with photocatalytic ability is subjected to temperature-sensitive calcination, the calcination temperature is 450-550°C, and the time is controlled within 2-4 hours; S1.2 After calcination, the carbonized nitrogen is pickled with HCl or H2SO4 solution, the pickling time is 30-60 minutes, and the pickling pH value is controlled within 1-4; S1.3 After pickling, the carbonized nitrogen is washed with deionized water until the carbonized nitrogen material has a neutral pH, and then dried for use;
[0018] S2. Combination of Nitrogen Carbonate and Titanium Dioxide Nanoparticles:
[0019] S2.1 The modified carbonized nitrogen is mixed with titanium dioxide nanoparticles, and the particle size of titanium dioxide is controlled to be 10-100 nanometers; S2.2 A mechanical stirrer is used to stir at a speed of 100-300 rpm for 1-2 hours to ensure that the carbonized nitrogen and titanium dioxide are fully mixed; S2.3 During the mixing process, ultrasonic treatment is performed by ultrasonic oscillation equipment at a frequency of 20-40kHz and a duration of 30-60 minutes to make the titanium dioxide particles evenly distributed on the surface of the carbonized nitrogen to form a composite photocatalytic material;
[0020] S3, attached metal ions:
[0021] S3.1 Place the composite photocatalytic material in a solution containing metal ions, where the metal ions are Zn 2+ , Cu 2+ 、Co 2+ One or more of the above, with a concentration range of 0.01-0.1M; S3.2 using ultrasound to treat the metal ion solution, the ultrasound frequency is 20-40kHz, and the treatment time is 30-60 minutes to ensure that the metal ions are uniformly attached to the surface of the composite material; S3.3 after the treatment, taking out the composite material from the metal ion solution, washing it with deionized water to remove unbound metal ions, and then drying it for later use;
[0022] S4. Soaking artificial fibers:
[0023] S4.1 Select polypropylene fiber, non-woven fabric or cotton material to make biological rope-like artificial fiber, and the diameter of the fiber is controlled to be 0.1-0.5 mm; S4.2 Soak the artificial fiber in the prepared composite photocatalytic colloid to ensure that all fibers are fully covered, and the soaking time is 48 hours; S4.3 During this period, maintain the temperature at 20-25°C to ensure that the photocatalytic material is fully combined with the fiber;
[0024] S5, high temperature drying:
[0025] S5.1 Take the soaked artificial fiber out of the photocatalytic colloid and dry it in a constant temperature drying oven; S5.2 Set the drying temperature to 100-150°C for 3-5 hours to ensure that the photocatalytic material is firmly attached to the fiber surface; S5.3 After drying, the composite nano-photocatalytic water grass fiber is naturally cooled and cut into a length suitable for use, ready for water purification.
[0026] Preferably, in S1.2, in the pickling step, the specific composition of the pickling solution is 3% to 5% HCl solution or H2SO4 solution, the temperature range of the pickling process is 30°C to 40°C, and the pickling duration is 45 to 60 minutes.
[0027] Preferably, in S2.2, during mechanical stirring, the rotation speed ranges from 150 to 250 rpm, and the stirring duration is 90 to 120 minutes; during the stirring process, the temperature needs to be maintained at 25°C to 35°C to promote the uniform combination of titanium dioxide nanoparticles and carbonitriding nitrogen; after the stirring is completed, the unreacted titanium dioxide particles are removed by centrifugal separation technology.
[0028] Preferably, in S3.3, the metal ion attachment process adopts a multiple immersion method, each immersion lasts for 15 to 30 minutes, and the saturation of ion attachment is monitored by measuring the conductivity of the metal ion solution during the immersion process; the final metal ion loading in the composite material is 1 to 3% of the total mass of the material.
[0029] Preferably, in S5.1, before drying, vacuum filtration is used to remove excess photocatalytic colloid; the moisture content of the fiber after filtration is controlled below 10%, the temperature during the drying process is controlled at 100°C to 150°C, the drying time is controlled at 3 to 5 hours, and after drying, the fiber is placed in a sealed environment to cool to room temperature.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention achieves the effect of efficient photocatalytic degradation of organic pollutants under natural light by setting a photocatalytic structure of a composite of carbonized nitrogen and titanium dioxide nanoparticles, significantly improves the photocatalytic efficiency, and overcomes the problem that existing photocatalytic materials are highly dependent on ultraviolet light.
[0032] 2. The present invention adopts the process of multiple immersion and ultrasonic treatment to attach metal ions, which effectively improves the stability of the composite photocatalytic material and avoids the deposition and aggregation of the material in the water body, and is particularly suitable for long-term purification of flowing water bodies.
[0033] 3. The artificial fiber substrate (polypropylene, non-woven fabric, cotton fiber) structure of the present invention is not only easy to operate and install, but also can maintain the uniform distribution of the material in the flowing water body, and enhances the adhesion of the photocatalytic material and prolongs the service life.
[0034] 4. The photocatalytic water grass fiber of the present invention is safe and non-toxic to the environment and aquatic organisms during the application process, has passed the CMA and CNAS biosafety tests, avoids secondary pollution problems, meets environmental protection requirements, and is suitable for large-scale water pollution control. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic diagram of the composition structure of the photocatalytic water grass fiber of the present invention;
[0036] Figure 2 This is a diagram showing the component content range of the photocatalytic water grass fiber of the present invention;
[0037] Figure 3 This is a diagram of the physical property parameters of the photocatalytic water grass fiber of the present invention;
[0038] Figure 4 This is a flow chart for preparing the photocatalytic water grass fiber of the present invention;
[0039] Figure 5 It is a specific process parameter diagram of the pickling step of the present invention;
[0040] Figure 6 It is a process parameter diagram of the mechanical stirring process of the present invention;
[0041] Figure 7 This is a schematic diagram of the metal ion attachment process of the present invention;
[0042] Figure 8 This is a flow chart of the drying process of the photocatalytic water grass fiber of the present invention. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] See also Figures 1 to 8 The present invention provides a photocatalytic water grass fiber for improving the water quality of flowing water bodies. The fiber is mainly composed of three components: a photocatalytic active component group, a function enhancement component group and a fiber substrate component group. The specific composition and function of each component group are as follows:
[0045] 1. Photocatalytic active component group: carbonized nitrogen and titanium dioxide nanoparticles. The photocatalytic active component is the core of the invention and is mainly used for the degradation of organic pollutants in water. The main materials in this component group are carbonized nitrogen (g-C3N4) and titanium dioxide nanoparticles (TiO2).
[0046] Carbonized nitrogen is a new type of photocatalytic material that can generate free radicals under the irradiation of natural light or visible light. These free radicals can react with organic pollutants in water and decompose harmful substances into harmless small molecules. This material has high photocatalytic efficiency and good stability, and is suitable for long-term use in water environments.
[0047] Titanium dioxide nanoparticles are a material widely used in the field of photocatalysis, especially for water purification. Titanium dioxide nanoparticles can produce highly active free radicals under light, have strong oxidizing ability, and can effectively degrade organic matter, bacteria and algae in water. Combining titanium dioxide nanoparticles with carbonized nitrogen can further improve the photocatalytic efficiency, because the two materials can form a synergistic effect and work under different wavelengths of light, thereby maximizing the use of natural light sources to improve water quality.
[0048] 2. Functional enhancement component group: metal ions. In this invention, the functional enhancement component group mainly enhances the effect of the photocatalytic reaction by introducing metal ions. The metal ions include Zn 2+ (Zinc ion), Cu 2+ (copper ions) and Co 2+ (Cobalt ions), their roles in photocatalytic water grass fibers are as follows:
[0049] Metal ions can enhance the photocatalytic effect in two ways. First, they can capture electrons or holes generated in the photocatalytic reaction, prevent the electrons and holes from recombination prematurely, and improve the efficiency of the reaction; second, metal ions themselves have certain catalytic activity and can participate in the reaction, further accelerating the degradation process of organic pollutants. 2+ , Cu 2+ and Co 2 + These three metal ions each have unique electrochemical properties, can exist stably under different reaction conditions, and promote the degradation of pollutants through complex reaction pathways. 2+ It can enhance the ultraviolet light absorption ability of titanium dioxide, while Cu 2+ and Co 2+ It can effectively participate in the reaction of visible light.
[0050] 3. Fiber substrate component group: polypropylene fiber, non-woven fiber, cotton fiber. The photocatalytic water grass fiber in the present invention uses polypropylene fiber, non-woven fiber and cotton fiber as carriers. These materials have good mechanical strength and chemical stability, can maintain their structure in water for a long time, and provide a stable attachment base for photocatalytic materials. Polypropylene fiber has strong chemical corrosion resistance and aging resistance, so it can maintain a long service life in flowing water. Since polypropylene material is relatively lightweight, the use of this fiber can ensure that the water grass fiber maintains good buoyancy in water. Non-woven fiber is a material with good water permeability and adsorption capacity, which can help the photocatalytic material to be more evenly distributed on the fiber surface, thereby increasing the area of its catalytic reaction. Cotton fiber has natural biocompatibility and good water absorption, which can further enhance the adsorption performance of the material in water, and form complementary structural advantages with other fiber materials, so that the entire photocatalytic water grass fiber can function stably in different water environments.
[0051] 4. The overall structure and principle of the photocatalytic water grass fiber. The photocatalytic water grass fiber is a fiber material that artificially simulates the shape of water grass. Its main function is to replace natural water grass in the water body and is used to remove organic pollutants and other harmful substances in the water. By loading the photocatalytic material (nitrogen carbide and titanium dioxide nanoparticles) on the fiber substrate and through the enhancement of metal ions, the photocatalytic water grass fiber of the present invention can continuously carry out photocatalytic reactions under natural light conditions.
[0052] After these fiber materials are placed in the water, they can use the light energy generated when natural light shines on the water to start the photocatalytic reaction. The photocatalytic materials can decompose organic pollutants in the water, such as organic dyes, drug residues, ammonia nitrogen and total phosphorus, thereby achieving the purpose of water purification. At the same time, the lightweight and durable characteristics of the fiber structure design ensure the long-term stability of the material in flowing water.
[0053] The present invention provides a photocatalytic water grass fiber for improving the water quality of flowing water bodies, wherein the content range of each component is carefully designed to ensure the best photocatalytic effect and long-term stability of the material. The details are as follows:
[0054] 1. Carbonized nitrogen (g-C3N4) content: 50%-70%
[0055] Carbonized nitrogen (g-C3N4) is used as the main photocatalytic active material of the present invention, and its content range is set to 50%-70%. This ratio ensures that the photocatalytic material can perform efficient photocatalytic reaction under visible light.
[0056] Function of carbonized nitrogen: Carbonized nitrogen is a material with good photocatalytic properties. Under natural light or artificial light, it can effectively absorb light energy and generate free radicals, which can further degrade organic pollutants in water, such as pesticide residues, dye wastewater and industrial pollutants. Carbonized nitrogen has a high photocatalytic efficiency. Within the content range of 50%-70%, it can not only ensure sufficient photocatalytic reaction area, but also maintain good synergy with other components.
[0057] The upper limit of the carbonized nitrogen content is 70% to ensure its dominant role in the material; the lower limit is 50% to maintain the mechanical strength and operability of the material and avoid the material being too fragile or losing structural stability in flowing water.
[0058] 2. Titanium dioxide nanoparticles (TiO2) content: 20%-40%
[0059] Titanium dioxide (TiO2) is another important photocatalytic material, which is widely used in the field of photocatalytic degradation of organic matter. The content of titanium dioxide is set to 20%-40% in the present invention, so that it and carbonized nitrogen together form an efficient photocatalytic system.
[0060] Role of titanium dioxide: Titanium dioxide is an excellent photocatalyst, especially with high photocatalytic activity under ultraviolet light. Titanium dioxide nanoparticles have a small particle size and a large specific surface area, which can provide more reactive sites and participate in the photocatalytic decomposition of pollutants together with carbonized nitrogen. Within the content range of 20%-40%, titanium dioxide can effectively form a synergistic effect with carbonized nitrogen, further improving the photocatalytic performance of the entire material.
[0061] The upper limit of titanium dioxide content is 40%, ensuring sufficient photocatalytic activity while avoiding excessive titanium dioxide causing material deposition or reduced dispersibility; the lower limit is 20%, ensuring a balanced ratio with carbonized nitrogen and avoiding a weakening of the catalytic effect of the material under visible light conditions.
[0062] 3.Metal ion content: 0.1%-5%
[0063] The present invention also introduces metal ions (Zn 2+ , Cu 2+ 、Co 2+ ) As a function-enhancing component, the content range of metal ions is set to 0.1%-5%, and this range is designed to improve the efficiency of the photocatalytic reaction.
[0064] Role of metal ions: Metal ions can improve the photocatalytic efficiency by capturing electrons or holes generated during the photocatalytic reaction and preventing them from prematurely recombination. Zn 2+ , Cu 2+ and Co 2+It can not only enhance the photocatalytic reaction efficiency of titanium dioxide and nitrogen carbide, but also further promote the decomposition of pollutants through its own electrochemical properties.
[0065] The upper limit of the metal ion content is 5%, ensuring that the photocatalytic material does not affect its mechanical properties or structural stability when working efficiently; the lower limit is 0.1%, ensuring that a small amount of metal ions can play a significant role without excessively affecting the economy or operability of the material.
[0066] 4. Polypropylene fiber content: 10%-20%
[0067] The polypropylene fiber is the main component of the fiber substrate, and the content range is set to 10%-20%. This ratio ensures that the photocatalytic material has good dispersibility and mechanical strength in the water body.
[0068] Function of polypropylene fiber: Polypropylene fiber has good chemical stability and corrosion resistance, and can maintain its structure unchanged in water for a long time. As a substrate, the high strength of polypropylene fiber can support the photocatalytic active ingredients and maintain the flexibility of the fiber, ensuring its good floating and distribution in flowing water.
[0069] The 10%-20% content range ensures that the material has sufficient mechanical strength and buoyancy in water bodies to remain in water bodies for a long time without settling due to excessive weight.
[0070] 5. Non-woven fabric fiber content: 5%-15%
[0071] The content range of the non-woven fabric fibers is set to 5%-15%, which is based on the consideration of the adsorption capacity and water permeability of the non-woven fabric fibers.
[0072] The role of non-woven fibers: Non-woven fibers have good adsorption and water permeability, which can help photocatalytic materials be evenly distributed on the fiber surface and ensure that water can flow smoothly through the fiber structure, increasing the contact area between pollutants and photocatalytic materials.
[0073] The ratio range of 5%-15% can ensure that the nonwoven fibers provide sufficient adsorption capacity and structural stability without excessively increasing the weight of the material and affecting its buoyancy in water.
[0074] 6. Cotton fiber content: 5%-10%
[0075] The content of the cotton fiber is set in the range of 5%-10%, which enables the material to have good water absorption and biocompatibility.
[0076] The role of cotton fiber: Cotton fiber has natural water absorption and good biocompatibility, which can further improve the water absorption capacity of photocatalytic materials, allowing photocatalytic reactions to be carried out more efficiently in a more humid environment. At the same time, the natural flexibility and tensile strength of cotton fibers also contribute to the mechanical stability of the overall material.
[0077] The 5%-10% content ensures that the material has sufficient water absorption and flexibility in water bodies and will not affect the mechanical properties and service life of the fiber.
[0078] The present invention further defines the specific physical properties of the photocatalytic water grass fiber, and the selection and control of these parameters play a crucial role in the photocatalytic performance, material stability and service life.
[0079] 1. The particle size range of titanium dioxide nanoparticles: 10 nanometers to 30 nanometers
[0080] Titanium dioxide (TiO2) is one of the core photocatalytic active materials of photocatalytic water grass fiber, and its particle size range has an important influence on the photocatalytic efficiency. In the present invention, the particle size of titanium dioxide nanoparticles is controlled between 10 nanometers and 30 nanometers.
[0081] The effect of particle size on photocatalytic effect: the smaller the particle size, the larger the specific surface area, and the more reactive sites provided, so that it can more efficiently contact with pollutants and participate in degradation reactions. Nano-scale titanium dioxide is in the range of 10-30 nanometers, which can not only maintain a high photocatalytic efficiency, but also effectively prevent particles from settling or agglomerating in water bodies and maintain good dispersibility.
[0082] The reason for setting the particle size range: 10 nanometers is the minimum particle size to ensure that TiO2 nanoparticles can still be highly efficient in catalysis, and 30 nanometers is the upper limit to ensure that the material still has good photocatalytic performance and dispersibility. Within this range, titanium dioxide can maximize the use of light energy and remain stably suspended in flowing water, avoiding particle aggregation and reducing catalytic efficiency.
[0083] 2. Specific surface area of carbonized nitrogen (g-C3N4): 80 to 100 m 2 / g, particle size: 10 microns to 20 microns
[0084] Carbon nitride (g-C3N4) is another key photocatalytic material, whose specific surface area and particle size determine the photocatalytic activity and stability of the material.
[0085] The role of specific surface area: The specific surface area directly determines the number of active sites of the material. The specific surface area range of carbonized nitrogen is set to 80 to 100 m 2 / g, which can provide sufficient reaction sites and increase the contact area with pollutants in water. The higher specific surface area can also improve the photocatalytic efficiency of carbonized nitrogen, ensuring that it has a good catalytic effect under visible light and natural light.
[0086] The role of particle size: The particle size of carbonized nitrogen is controlled between 10 microns and 20 microns. The particles in this range are small enough to be evenly distributed on the fiber substrate, while avoiding the material deposition problem caused by excessive particle size. 10 microns is the minimum particle size to ensure that carbonized nitrogen works effectively in the photocatalytic process, while the upper limit of 20 microns ensures that it still has sufficient photocatalytic activity and will not be unevenly dispersed in the water due to excessive particle size.
[0087] 3. Metal ion loading: 85% to 95% of the total mass of the composite material
[0088] The introduction of metal ions is to enhance the efficiency of the photocatalytic material, and the control of the loading amount has an important influence on the material performance. In the present invention, the loading amount of the metal ions is controlled to be 85% to 95% of the total mass of the composite material.
[0089] Effect of loading amount: The loading amount of metal ions directly affects the photocatalytic activity of the material. Too little loading amount cannot fully exert the enhancing effect of metal ions in the photocatalytic reaction, while too high loading amount may affect the structural stability of the composite material or cause the reaction sites on the surface of the photocatalytic material to be over-covered, which in turn reduces the catalytic efficiency. Therefore, the loading amount is controlled within the range of 85% to 95% to ensure that the metal ions can effectively attach to the surface of the photocatalytic material without having a negative impact on the performance of the material.
[0090] Reasons for setting: 85% is the lower limit to ensure that enough metal ions participate in the photocatalytic reaction, while 95% is the upper limit to avoid over-saturation of the material and ensure that the metal ions can be evenly distributed in the composite material.
[0091] 4. The diameter range of polypropylene fiber: 0.3 mm to 0.5 mm
[0092] Polypropylene fiber is one of the base materials of photocatalytic waterweed fiber, and its diameter directly affects the mechanical strength of the fiber and the suspension stability in the water body. The diameter range is set to 0.3 mm to 0.5 mm.
[0093] Effect of diameter on performance: Polypropylene fibers with smaller diameters can provide a softer material texture, making it easier for the fibers to float and disperse in the water, increasing the contact area with pollutants in the water. Polypropylene fibers with larger diameters can provide better mechanical strength, ensuring that the material can be used stably for a long time in flowing water and is not easily damaged by water flow.
[0094] Reason for setting: 0.3 mm is the lower limit to ensure that the fiber still has good mechanical properties, while the upper limit of 0.5 mm ensures that the material can maintain good flexibility and buoyancy in the water, avoiding the fiber from sinking due to excessive weight.
[0095] 5. Water absorption of non-woven fabric fibers: 90% to 95% of its weight
[0096] The non-woven fabric fiber plays a role in enhancing the water absorption of the material in the present invention, and its water absorption rate is set to 90% to 95%. This range ensures that the material can effectively absorb pollutants in the water body.
[0097] The role of water absorption: The high water absorption of non-woven fibers ensures that the material can quickly absorb water in the water and remain moist, which helps the photocatalytic reaction to continue. At the same time, fibers with good water absorption can distribute the photocatalytic material more evenly in the water, ensuring that it is fully in contact with pollutants in the water.
[0098] Reason for setting: 90% is the lower limit to ensure that the material has sufficient water absorption, and 95% is the upper limit to prevent the material from absorbing too much water and causing the fiber structure to deform or lose stability.
[0099] The preparation method of photocatalytic water grass fiber includes multiple steps, which respectively involve the modification of carbonized nitrogen, the combination with titanium dioxide nanoparticles, the attachment of metal ions, the soaking of artificial fibers and high-temperature drying. Each step provides essential performance support for the final photocatalytic water grass fiber, as follows:
[0100] S1. Modification of carbonitride
[0101] Carbonized nitrogen is the core photocatalytic material in the photocatalytic water grass fiber, and its photocatalytic performance can be improved after modification. In step S1, carbonized nitrogen is calcined and acid-washed to enhance its surface activity and structural stability.
[0102] S1.1 Calcination treatment
[0103] The calcination temperature is set at 450-550℃ and the time is controlled at 2-4 hours. This temperature and time range can fully activate the photocatalytic ability of the carbonized nitrogen material and optimize its pore structure to give it a larger specific surface area. Too low a temperature may lead to insufficient carbonized nitrogen activity, while too high a temperature may lead to excessive sintering of the material and reduce its catalytic efficiency.
[0104] S1.2 Pickling treatment
[0105] The calcined carbonized nitrogen needs to be pickled using HCl or H2SO4 solution for 30-60 minutes, with the pH value during the pickling process controlled between 1 and 4. The role of pickling is to remove impurities in the material, expose more active sites, and optimize the surface structure of carbonized nitrogen through acid treatment, further enhancing its photocatalytic ability.
[0106] S1.3 Cleaning and drying
[0107] After pickling, the carbonized nitrogen must be fully washed with deionized water until the pH value of the material returns to neutral to prevent acid residues from affecting the bonding performance of subsequent materials. The washed carbonized nitrogen is dried for use to ensure that the material can effectively bind other components in subsequent steps.
[0108] S2. Combination of Nitrogen Carbonate and Titanium Dioxide Nanoparticles
[0109] In step S2, carbonized nitrogen is combined with titanium dioxide nanoparticles to form a composite photocatalytic material. The particle size of titanium dioxide is controlled to be 10-100 nanometers to ensure that it has sufficient specific surface area and reaction activity.
[0110] S2.1 Material Mixing
[0111] The mixing process of carbonized nitrogen and titanium dioxide uses mechanical stirring, and the speed of the stirrer is set at 100-300 rpm and the stirring time is 1-2 hours to ensure that the two materials are fully mixed. Temperature control during the stirring process is also a key factor. Maintaining a uniform temperature can ensure mixing uniformity.
[0112] S2.2 Ultrasonic treatment
[0113] In order to further ensure that the titanium dioxide particles are evenly distributed on the surface of carbonized nitrogen, ultrasonic oscillation equipment is used for treatment. The ultrasonic frequency is set to 20-40kHz and the treatment time is 30-60 minutes. Ultrasonic treatment can effectively break the agglomeration between particles, promote the close combination of titanium dioxide particles and carbonized nitrogen, and form a highly active photocatalytic composite material.
[0114] S3, attached metal ions
[0115] Step S3 is to add metal ions (Zn 2+ , Cu 2+ 、Co 2+ ) are loaded onto the composite photocatalytic material to further enhance the photocatalytic ability of the material.
[0116] S3.1 Addition of metal ions
[0117] The composite photocatalytic material was placed in a Zn 2+ , Cu 2+or Co 2+ The concentration of the solution is controlled at 0.01-0.1 M. The introduction of metal ions can capture electrons or holes, prolong the reaction time, and thus improve the photocatalytic efficiency.
[0118] S3.2 Ultrasonic treatment of metal ion solutions
[0119] In order to ensure that the metal ions can be evenly attached to the surface of the composite material, ultrasonic treatment is used with a frequency of 20-40kHz and a treatment time of 30-60 minutes. Ultrasonic waves can increase the contact opportunities between metal ions and materials, ensuring uniform loading effects.
[0120] S3.3 Cleaning and drying
[0121] After the metal ion loading is completed, the material is washed with deionized water to remove unbound metal ions and prevent excess metal ions from affecting the structure and photocatalytic properties of the material. The washed material needs to be dried for use in preparation for the next fiber soaking process.
[0122] S4. Soaking artificial fibers
[0123] In step S4, the treated photocatalytic composite material will be attached to the artificial fiber to form a water grass fiber structure.
[0124] S4.1 Selection of artificial fibers
[0125] In the present invention, polypropylene fiber, non-woven fabric or cotton material is used as the biological rope-like artificial fiber. The diameter of the fiber is controlled within 0.1-0.5 mm, which ensures that the fiber has good mechanical strength and flexibility and can adapt to the fluidity in the water body.
[0126] S4.2 Photocatalytic colloid immersion
[0127] The artificial fiber is completely immersed in the prepared photocatalytic colloid for 48 hours to ensure that the photocatalytic material can be evenly attached to the fiber surface. The temperature during the immersion process is controlled at 20-25°C to maintain the structural stability of the material and ensure the uniform attachment of the photocatalytic material.
[0128] S5, high temperature drying
[0129] The last step is to dry the soaked photocatalytic water grass fiber at high temperature to ensure that the material is firmly attached to the fiber surface and has long-term stable performance.
[0130] S5.1 Drying treatment
[0131] The soaked fiber is taken out from the photocatalytic colloid and placed in a constant temperature drying oven with the drying temperature set at 100-150°C for 3-5 hours. This temperature range ensures that the photocatalytic material is fully dried without destroying the physical structure of the fiber.
[0132] S5.2 Natural cooling
[0133] After drying, the photocatalytic water grass fiber needs to go through a natural cooling process to prevent the material from cracking or other mechanical damage during the rapid cooling process. After cooling, the fiber is cut into suitable lengths for use and is ready for water purification.
[0134] Specific process parameters for the pickling step
[0135] In step S1.2, acid washing treatment is crucial to remove impurities in the carbonitride material and improve the surface activity and photocatalytic performance of the material.
[0136] The composition of the pickling solution: 3% to 5% HCl solution or H2SO4 solution. The pickling solution uses 3%-5% HCl (hydrochloric acid) or H2SO4 (sulfuric acid). This range is based on the experimental results of material cleaning and surface activity improvement. If the acid concentration is too low, it will not be able to effectively remove impurities and oxide layers on the surface of carbonized nitrogen; while if the acid concentration is too high, it may cause excessive corrosion on the surface of the material and damage its structural stability. Therefore, the acid solution concentration of 3%-5% can maintain the integrity of the carbonized nitrogen surface while removing impurities.
[0137] The temperature of the pickling process: 30℃ to 40℃, the temperature is controlled between 30℃ and 40℃, this temperature range helps to increase the reaction rate of the acid solution and promote the exposure of the active sites on the surface of the carbonized nitrogen. Too low a temperature may cause the pickling reaction to be too slow and the cleaning to be insufficient; too high a temperature may accelerate the degradation of the material and affect the physical properties of the carbonized nitrogen.
[0138] Pickling time: 45 to 60 minutes. Control of the pickling time is also a key factor in optimizing the surface structure of carbonized nitrogen. If the pickling time is too short, impurities and surface oxides will not be removed thoroughly; if the pickling time is too long, it may have a negative impact on the photocatalytic activity of the material. The time range of 45-60 minutes ensures that the material is fully cleaned during the pickling process without destroying its microstructure. With these optimized parameters, carbonized nitrogen has higher surface activity and specific surface area after pickling, which is helpful for the subsequent loading of titanium dioxide and the improvement of photocatalytic performance;
[0139] The key parameters of mechanical stirring in step S2.2 include speed, time, temperature control, etc. to ensure the full combination of nitrogen carbide and titanium dioxide nanoparticles.
[0140] Stirring speed: 150 to 250 rpm. During the material mixing process, the stirring speed determines the mixing uniformity. The speed range of 150 to 250 rpm can ensure uniform dispersion of carbonized nitrogen and titanium dioxide particles. Too low a speed may lead to uneven mixing and particle agglomeration; too high a speed may cause damage to titanium dioxide particles or structural damage to carbonized nitrogen materials. Therefore, this range is the best range to ensure uniform mixing of materials and maintain structural integrity.
[0141] Stirring duration: 90 to 120 minutes. The control of stirring time is also critical. A stirring time of 90 to 120 minutes can ensure sufficient material mixing time so that titanium dioxide particles are evenly distributed on the surface of carbonitride. Too short a time may lead to insufficient material mixing, affecting the performance of the photocatalytic material; too long a time may cause material friction loss and reduce the photocatalytic efficiency.
[0142] Stirring temperature: 25℃ to 35℃. The temperature during stirring is controlled between 25℃ and 35℃. This temperature range can effectively promote the combination of titanium dioxide nanoparticles and carbonized nitrogen. Too low temperature will reduce the reaction rate and the material combination will not be sufficient; too high temperature may cause decomposition or chemical reaction of the material, affecting its catalytic activity.
[0143] Centrifugal separation technology removes unreacted titanium dioxide particles. After stirring, centrifugal separation technology is used to remove unreacted titanium dioxide particles to ensure that the mixed material contains only uniformly combined photocatalytic materials. This step avoids unnecessary deposition of excess titanium dioxide in the water body and ensures that the final photocatalytic composite material remains well suspended and dispersed in the water body.
[0144] In step S3.3, the attachment process of metal ions is crucial to the photocatalytic efficiency of the composite material. Multiple immersion methods and conductivity monitoring technology are used to ensure uniform attachment of metal ions and control their loading within the range of 1% to 3% of the total mass of the material.
[0145] Multiple immersion method: The metal ion attachment process adopts multiple immersion method, and each immersion lasts for 15 to 30 minutes. The purpose of multiple immersion is to gradually increase the loading amount of metal ions and ensure that the ions can be evenly distributed on the surface of the composite photocatalytic material. If only one immersion is used, it may cause uneven attachment of metal ions and affect the photocatalytic performance of the material. Through multiple immersions, the ion attachment process is more stable, which improves the stability and catalytic effect of the composite material.
[0146] Conductivity monitors the saturation of ion attachment. During each immersion process, conductivity is used to monitor the state of the metal ion solution. Changes in conductivity can reflect changes in the concentration of metal ions in the solution. By measuring conductivity, the ion attachment process can be monitored to ensure that the composite material reaches a saturated attachment state. When the conductivity drops to a stable value, it means that the ions in the solution have been basically adsorbed by the composite material. This monitoring method can effectively avoid excessive or insufficient ion attachment.
[0147] Metal ion loading control: 1% to 3%, the final metal ion loading is controlled within the range of 1% to 3% of the total mass of the material. The loading within this range can effectively improve the photocatalytic activity of the material while avoiding excessive loading leading to unstable material structure or metal ion desorption problems. The lower limit of 1% ensures sufficient ion attachment, and the upper limit of 3% avoids the negative impact of excessive ion loading on material stability and reaction performance.
[0148] In step S5.1, the handling of the material before drying and the control of temperature and humidity during drying have a direct impact on the quality of the final product.
[0149] Vacuum filtration to remove excess photocatalytic colloids. Before drying, vacuum filtration is used to remove excess photocatalytic colloids. Excessive residual photocatalytic colloids may affect the structural stability of the fiber and the uniformity of the surface photocatalytic material. Through vacuum filtration, excess liquid components can be quickly and effectively removed to ensure that only an appropriate amount of photocatalytic material is retained on the fiber surface, while preventing excessive accumulation of colloids between fibers, thereby improving the dispersibility of the material in the water.
[0150] The moisture content is controlled below 10%, and the moisture content of the fiber after vacuum filtration needs to be controlled below 10%. This standard ensures that the material will not shrink or break due to excessive evaporation of water during the drying process. At the same time, maintaining a low moisture content helps to steadily remove the remaining moisture during the drying process without destroying the bond between the photocatalytic material and the fiber substrate.
[0151] Drying temperature: 100℃ to 150℃, time: 3 to 5 hours, the drying temperature is set at 100℃ to 150℃, and the drying time is controlled to 3 to 5 hours. This temperature range is sufficient to remove the remaining moisture while ensuring the stable attachment of the photocatalytic material. Too low a temperature may result in insufficient moisture removal, and residual liquid may still remain on the surface of the material; too high a temperature may damage the structure and photocatalytic properties of the fiber material. The time interval of 3 to 5 hours ensures the gradual drying process of the material, so that the moisture inside and on the surface of the material is evenly removed.
[0152] Cooling after drying: After drying, the fiber needs to cool naturally to room temperature in a sealed environment. This process helps prevent cracks or other structural damage to the material when the temperature drops sharply. The sealed environment can isolate the outside moisture and prevent the newly dried material from reabsorbing moisture from the air, ensuring its stability.
[0153] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A photocatalytic water grass fiber for improving the water quality of flowing water, characterized in that: The photocatalytic water grass fiber is composed of the following components: Photocatalytically active component group: carbonized nitrogen, titanium dioxide nanoparticles; Function-enhancing ingredient group: metal ions; Fiber substrate component group: polypropylene fiber, non-woven fiber, cotton fiber; The metal ions include Zn 2+ , Cu 2+ and Co 2+ .
2. The photocatalytic water grass fiber for improving the water quality of flowing water according to claim 1, characterized in that: The photocatalytic water grass fiber includes the following components in content range: Carbonized nitrogen: 50%-70%; Titanium dioxide nanoparticles: 20%-40%; Metal ions: 0.1%-5%; Polypropylene fiber: 10%-20%; Non-woven fabric fiber: 5%-15%; Cotton fiber: 5%-10%.
3. The photocatalytic water grass fiber for improving the water quality of flowing water according to claim 1, characterized in that: The specific content range of the optimized formula of the photocatalytic water grass fiber is: Carbonized nitrogen: 55%-65%; Titanium dioxide nanoparticles: 25%-35%; Metal ions: 1%-3%; Polypropylene fiber: 12%-18%; Non-woven fabric fiber: 8%-12%; Cotton fiber: 5%-8%.
4. The photocatalytic water grass fiber for improving the water quality of flowing water according to claim 1, characterized in that: The particle size of the titanium dioxide nanoparticles ranges from 10 nanometers to 30 nanometers; The specific surface area of the carbonized nitrogen is 80 to 100 m 2 / g, and its particle size is 10 microns to 20 microns; The loading amount of the metal ions is 85% to 95% of the total mass of the composite material; The diameter of the polypropylene fiber ranges from 0.3 mm to 0.5 mm; The water absorption rate of the nonwoven fabric fibers is 90% to 95% of its weight.
5. A method for preparing a photocatalytic water grass fiber for improving the water quality of a flowing water body, applied to the photocatalytic water grass fiber for improving the water quality of a flowing water body as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Modification of carbonitride: S1.1 The carbonized nitrogen material with photocatalytic ability is subjected to temperature-sensitive calcination at a temperature of 450-550°C for a time of 2-4 hours; S1.2 After calcination, the carbonized nitrogen is pickled with HCl or H2SO4 solution for 30-60 minutes, and the pickling pH value is controlled at 1-4; S1.3 After pickling, the carbonized nitrogen is washed with deionized water until the carbonized nitrogen material has a neutral pH, and then dried for later use; S2. Combination of Nitrogen Carbonate and Titanium Dioxide Nanoparticles: S2.1 mixing the modified carbonized nitrogen with titanium dioxide nanoparticles, wherein the particle size of the titanium dioxide is controlled to be 10-100 nanometers; S2.2 Use a mechanical stirrer to stir at a speed of 100-300 rpm for 1-2 hours to ensure that the carbonized nitrogen and titanium dioxide are fully mixed; S2.3 During the mixing process, ultrasonic treatment is performed by ultrasonic oscillation equipment at a frequency of 20-40 kHz and a duration of 30-60 minutes to make the titanium dioxide particles evenly distributed on the surface of the carbonitride to form a composite photocatalytic material; S3, attached metal ions: S3.1 Place the composite photocatalytic material in a solution containing metal ions, where the metal ions are Zn 2+ , Cu 2+ 、Co 2+ One or more of the following, with a concentration range of 0.01-0.1M; S3.2 Treat the metal ion solution with ultrasound at a frequency of 20-40 kHz for 30-60 minutes to ensure that the metal ions are evenly attached to the surface of the composite material; After treatment in S3.3, the composite material is taken out from the metal ion solution, washed with deionized water to remove unbound metal ions, and then dried for later use; S4. Soaking artificial fibers: S4.1 Use polypropylene fiber, non-woven fabric or cotton material to make biological rope-like artificial fiber, and the fiber diameter is controlled within 0.1-0.5 mm; S4.2 immerse the artificial fiber in the prepared composite photocatalytic colloid to ensure that all fibers are fully covered, and the immersion time is 48 hours; S4.3 During this period, the temperature is maintained at 20-25°C to ensure that the photocatalytic material is fully combined with the fiber; S5, high temperature drying: S5.1 taking the soaked artificial fiber out of the photocatalytic colloid and drying it in a constant temperature drying oven; S5.2 The drying temperature is set to 100-150°C for 3-5 hours to ensure that the photocatalytic material is firmly attached to the fiber surface; S5.3 After drying, the composite nano-photocatalytic water grass fiber is naturally cooled and then cut into suitable lengths for use, ready for water purification.
6. The method for preparing photocatalytic water grass fibers for improving the water quality of flowing water according to claim 5, characterized in that: In S1.2, in the pickling step, the specific composition of the pickling solution is 3% to 5% HCl solution or H2SO4 solution, the temperature range of the pickling process is 30°C to 40°C, and the pickling duration is 45 to 60 minutes.
7. The method for preparing photocatalytic water grass fibers for improving the water quality of flowing water according to claim 5, characterized in that: In S2.2, during mechanical stirring, the rotation speed ranges from 150 to 250 rpm, and the stirring duration is 90 to 120 minutes; during the stirring process, the temperature needs to be maintained at 25°C to 35°C to promote the uniform combination of titanium dioxide nanoparticles and carbonitriding nitrogen; after the stirring is completed, the unreacted titanium dioxide particles are removed by centrifugal separation technology.
8. The method for preparing photocatalytic water grass fibers for improving the water quality of flowing water according to claim 5, characterized in that: In S3.3, the metal ion attachment process adopts a multiple immersion method, each immersion lasts for 15 to 30 minutes, and the saturation of ion attachment is monitored by measuring the conductivity of the metal ion solution during the immersion process; the final metal ion loading in the composite material is 1 to 3% of the total mass of the material.
9. The method for preparing photocatalytic water grass fibers for improving the water quality of flowing water according to claim 5, characterized in that: In S5.1, before drying, vacuum filtration is used to remove excess photocatalytic colloid; the moisture content of the fiber after filtration is controlled below 10%, the temperature during the drying process is controlled at 100°C to 150°C, the drying time is controlled at 3 to 5 hours, and after drying, the fiber is placed in a sealed environment to cool to room temperature.
Citation Information
Cited By
Process for photocatalytically synthesizing hydrogen peroxide to resist algae
CN120136291A